2015
DOI: 10.2174/1570159x1304150831120428
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Pathological Mechanism and Drug Treatment Mechanism of Depression

Abstract: Depression is one of the prevalent and persistent psychiatric illnesses. It brings heavy socioeconomic burden such as healthcare expenditures and even higher suicide rates. Despite many hypotheses about its mechanism have been put forward, so far it is still unclear, not to mention the precise and effective diagnostic or therapeutic methods. In this paper, the current conditions of pathological and pharmacological mechanism of depression were reviewed systematically. Firstly, the most recent hypotheses and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(70 citation statements)
references
References 63 publications
0
63
0
Order By: Relevance
“…However, acute withdrawal from chronic psychostimulants induces allosteric load in HPA axis, elevates secretion of CRF and ACTH, and decreases cortisol levels, which are hallmarks of depressive and anxiety spectrum disorders in man ( Li et al ., 2013a ; Zuloaga et al ., 2015 ). However, in depressed patients, regulation of HPA axis is disrupted, which leads to low level of cortisol concentration in serum via stress reactivity ( Peng et al ., 2015 ). Surprisingly, hypercortisolemia is present in about 40%–60% of depressed adults ( Carroll et al ., 2007 ), which may explain the cause of disrupted hippocampal integrity and impaired memory function in the pathogenesis of depression.…”
Section: Relations Between Cart Containing Neural Circuits and Depresmentioning
confidence: 99%
“…However, acute withdrawal from chronic psychostimulants induces allosteric load in HPA axis, elevates secretion of CRF and ACTH, and decreases cortisol levels, which are hallmarks of depressive and anxiety spectrum disorders in man ( Li et al ., 2013a ; Zuloaga et al ., 2015 ). However, in depressed patients, regulation of HPA axis is disrupted, which leads to low level of cortisol concentration in serum via stress reactivity ( Peng et al ., 2015 ). Surprisingly, hypercortisolemia is present in about 40%–60% of depressed adults ( Carroll et al ., 2007 ), which may explain the cause of disrupted hippocampal integrity and impaired memory function in the pathogenesis of depression.…”
Section: Relations Between Cart Containing Neural Circuits and Depresmentioning
confidence: 99%
“…Despite the physiopathological mechanism of depression remaining not widely elucidated and unclear, numerous studies have shown a multifactorial origin, involving genetics, environmental, psychological, and social factors, as well as dysfunction in multiple brain areas such as the hippocampus, prefrontal cortex, nucleus accumbens, and amygdale [7][8][9][10]. Recent findings of the presence of inflammatory process and oxidative stress in the pathophysiology of depression provide new pathways and treatment targets for improvement of pharmacological approach in depression [11].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms such as low-level mood, loss of interest, lack of motivation, eating and sleeping problems, and couples of cognitive variations are diagnosed for depression disorder [2]. Although the main genetic initiation of depression has not been recognized yet, but pathophysiological monoamine hypothesis claims that the neurotransmitters changes in brain may lead to depression [3]. The monoamine oxidase (MAO) enzyme is available in two A and B forms, in which the MAO-A degenerates serotonin and norepinephrine leading to depression whereas MAO-B degenerates dopamine and betaphenylamine leading to Alzheimer [4,5].…”
Section: Introductionmentioning
confidence: 99%